2014
DOI: 10.1249/mss.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

The Muscle Stretch Reflex throughout the Menstrual Cycle

Abstract: Introduction The significant sex-disparity in sports-related knee injuries may be due to underlying differences in motor control. While the development of sex-specific movement patterns is likely multi-factorial, this study specifically focuses on the potential modulatory role of sex hormones. Purpose To investigate the muscle stretch reflex (MSR) across the menstrual cycle. We hypothesized that the MSR would fluctuate throughout the menstrual cycle, and that the lowest response would correspond with peak co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…This idea is supported by studies that have demonstrated associations of normal physiologic variations in sex hormone concentrations across the menstrual cycle with substantial changes in markers of collagen metabolism and production, 191 kneejoint laxity, [130][131][132][133][134][135] muscle stiffness, 131 and the musclestretch reflex. 192 These biological changes may also have secondary neuromechanical consequences, as previously noted. 155,156,[158][159][160] Although results from prior epidemiologic studies have suggested that the risk of an ACL injury appears to be greater during the preovulatory phase of the menstrual cycle compared with the postovulatory phase, [193][194][195][196][197] our understanding of the underlying mechanism for this increased likelihood has not advanced.…”
Section: Hormonal Risk Factorsmentioning
confidence: 81%
“…This idea is supported by studies that have demonstrated associations of normal physiologic variations in sex hormone concentrations across the menstrual cycle with substantial changes in markers of collagen metabolism and production, 191 kneejoint laxity, [130][131][132][133][134][135] muscle stiffness, 131 and the musclestretch reflex. 192 These biological changes may also have secondary neuromechanical consequences, as previously noted. 155,156,[158][159][160] Although results from prior epidemiologic studies have suggested that the risk of an ACL injury appears to be greater during the preovulatory phase of the menstrual cycle compared with the postovulatory phase, [193][194][195][196][197] our understanding of the underlying mechanism for this increased likelihood has not advanced.…”
Section: Hormonal Risk Factorsmentioning
confidence: 81%
“…The muscle stretch reflex and postural control seem to change over the menstrual cycle (Casey et al . ). Impaired postural control has been detected in the luteal phase when progesterone is high, but only in women with premenstrual symptoms (Fridén et al .…”
Section: Discussionmentioning
confidence: 97%
“…), while the muscle stretch reflex response seems to be lowest at this phase (Casey et al . ). Postural control has been reported to be impaired during the premenstrual phase (Darlington et al .…”
mentioning
confidence: 97%
“…In some studies, increased levels of progesterone in the luteal phase were related to increased intensity of premenstrual complaints (anxiety, tension, irritability) (6,7), while in other studies decreased progesterone levels were found to be related to more pronounced negative mood changes (8,9). Moreover, the neuromusculoskeletal effects relating to muscle strength and stretch reflex (10), ligament laxity (11), biomechanical characteristics (12), and postural control (13,14) throughout the menstrual cycle have been investigated in the literature in order to determine the relationship between injury mechanisms in women and the differences between the sexes. Menarche itself was declared to be a risk factor in some sports and conditions (15).…”
Section: Introductionmentioning
confidence: 99%